(untitled) (The Review of Diabetic Studies, 2023)
Microvascular function in patients with type 1 diabetes without chronic complications was assessed using skin capillary recruitment during post-occlusive reactive hyperemia (PORH). Structural (maximal) capillary density was evaluated during venous occlusion. The study included 48 consecutive outpatients aged 26.3 ± 10.8 years with type 1 diabetes (duration of 9.5 years) without chronic complications and 34 control subjects. Intravital capillary video-microscopy was used in the dynamic study of skin capillaries in the dorsum of the fingers and toes. Capillary recruitment during PORH (% increase in mean capillary density, MCD) was significantly higher in the controls than the patients in both the fingers (p < 0.001) and toes (p < 0.001). During venous occlusion, MCD increase was also higher in the controls than the patients in both the fingers (p < 0.05) and toes (p < 0.0001). In patients, no difference was found between MCD at baseline and after venous occlusion in the fingers but a decrease was observed in the toes (p < 0.001). It is concluded that skin capillary function is significantly impaired in both fingers and toes of patients with type 1 diabetes without chronic complications. Moreover, capillary density during venous occlusion did not increase in either extremity in the patients, suggesting that their capillaries at rest are already maximally recruited.